2009
DOI: 10.1063/1.3122665
|View full text |Cite
|
Sign up to set email alerts
|

Fabricating scaffolds by microfluidics

Abstract: In this paper, we demonstrate for the first time the technique to using microfluidics to fabricate tissue engineering scaffolds with uniform pore sizes. We investigate both the bubble generation of the microfluidic device and the application of foam as a tissue engineering scaffold. Our microfluidic device consists of two concentric tapered channels, which are made by micropipettes. Nitrogen gas and aqueous alginate solution with Pluronic ® F127 surfactant are pumped through the inner and the outer channels, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 29 publications
1
82
0
2
Order By: Relevance
“…In our system no surfactants or shell stabilizers were introduced, as they might have influenced the LC orientation 26 , which is the essential factor determining the actuation effect. The co-flow microfluidic geometry was specially chosen, as it allowed a good control of the preparation of coreshell particles 27,28 , and as coalescence of the particles can be avoided until they are photo-polymerized further downstream. The microfluidic device comprised a triple co-flow channel; a cylindrical glass micropipette was nested into a tapered square glass capillary, which was confined by teflon tubing.…”
Section: Resultsmentioning
confidence: 99%
“…In our system no surfactants or shell stabilizers were introduced, as they might have influenced the LC orientation 26 , which is the essential factor determining the actuation effect. The co-flow microfluidic geometry was specially chosen, as it allowed a good control of the preparation of coreshell particles 27,28 , and as coalescence of the particles can be avoided until they are photo-polymerized further downstream. The microfluidic device comprised a triple co-flow channel; a cylindrical glass micropipette was nested into a tapered square glass capillary, which was confined by teflon tubing.…”
Section: Resultsmentioning
confidence: 99%
“…1(b), uniform-sized bubbles packed in the crystalline state 74 were collected from the outlet into a PMMA-made reservoir. After degassed under vacuum, the interconnected pores were filled with water.…”
Section: Resultsmentioning
confidence: 99%
“…73 A majority of these methods involve complicated processes and/or expensive robots, so they are not suitable for massive scaffold fabrication. Recently, Lin et al 74 reported using simple microfluidics to easily and economically fabricate 3D scaffolds with uniform pore sizes by generating monodisperse foam with a microfluidic device.…”
Section: Introductionmentioning
confidence: 99%
“…Three dimensional scaffolds which have uniform pore size, shape, and spatial structures are highly sought after so that systematic studies on the architecture influence of the differences in signaling, gene expression, and organization can be conducted and chemical stimuli can be distributed more homogeneously. Chung et al recently demonstrated the use of microfluidics to fabricate tissue engineering scaffolds with uniform pore sizes based on bubble generation and the application of foam as the scaffold [40]. The microfluidic device was composed of two concentric tapered channels, which were made by micropipettes.…”
Section: Monodisperse Microbubblesmentioning
confidence: 99%
“…Normally, a low Ca (surface tension dominant) will tend to generate plugs, a medium Ca (shear force becomes larger) will tend to produce droplets, while a high Ca (shear force dominant) induces a laminar flow and the range of Ca describing each regime varies as water fraction (wf) changes. A variety of interesting applications to assemble a range of organic and inorganic micro-and nanomaterials inside the droplets, the plugs or along the interface of the laminar flow has been demonstrated including spherical janus for photonic crystals (polymeric microparticles) [12], liposomes for cell membrane study (polymeric lipid bilayer) [39], scaffolds for cell culture (microbubbles) [40], multicomponent nanoparticles for therapy and diagnosis (lipid-polymer and lipid-quantum dot nanoparticles) [41], etc.…”
Section: Free-flow Self-assemblymentioning
confidence: 99%